Campaña gráfica acerca de los beneficios sociales de la legalización del cannabis en el Ecuador - Benítez Cedeño, Carlos Vicente (2019)
The legalization of cannabis is an issue that has generated a debate in a national and international levels, due to its relevance in the illegal drug business and its impact on society. Currently it is banned in almost all the world, however, some countries have already legalized its use for therapeutic purposes, noting the changes that have occurred in several aspects shortly after the entry of their respective laws. The prohibition of cannabis has a direct and indirect impact on society where it is applied and creates prejudices around a plant that has the potential to have multiple uses, that is why it has been decided to inform the target audience through a graphic campaign about the social benefits that cannabis would bring to Ecuadorian society if it is legalized.